Rhinosporidiosis-an atypical presentation as a facial swelling in left cheek - Kumar, E. Siva; Swapna, C. A.; Karanam, Lavanya; Kumar, Ram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Rhinosporidiosis is a chronic granulomatous disease of mucous membranes caused by Rhinosporidium seeberi. Most frequently affected sites are nose and nasopharynx followed by eye. Report a rare case of 13-year-old female with rhinosporidiosis in a bizarre way of presentation as a cyst in left cheek. A 13-year-old female child hailing from West Bengal presented to ENT OPD with complaints of swelling in the left cheek for 6 months gradually increasing in size. On examination left side of cheek a cystic swelling extending from angle of mouth to lateral side of face was seen. Magnetic resonance imaging (MRI) neck plain and contrast showed large well defined T2 hyperintense cystic lesion in subcutaneous plane measuring about 5.7 cm (transverse)×6.0 cm (cephalocaudal)×5.5 cm (anteroposterior) with post contrast wall enhancement. Patient planned for excision and histopathological examination was consistent with rhinosporidiosis. Rhinosporidiosis continues to be a conundrum necessitating further literature and research on this. The difficulty in culturing the organism and its preternatural presentations add up to difficulties in diagnosing. Emphasise the quaint feature of its presentation as a cyst in cheek as primary site without any focus of infection in the respiratory tract and with negative history of traumatic inoculation.